“Most of Them Are Amateurs”: Women with Spinal Cord Injury Experience the Lack of Education and Training among Medical Providers While Seeking Gynecological Care - Dillaway, Heather Elise; Lysack, Catherine L. (Disability Studies Quarterly, 2015)
Although the American Disabilities Act (ADA, 1990) became federal law more than two decades ago, individuals with disabilities continue to experience substandard healthcare. We use this article to hone in on disabled women's experiences of seeking gynecological care and the access disparities they still face. The data for this qualitative study were gathered using in-depth interviews with 20 women living with spinal cord injuries in or around Detroit, Michigan. Each interviewee was questioned about overall health and physical functioning, accessibility of doctor offices, interactions with health care providers, and gynecological health-seeking behaviors. In this paper we report on women's gynecological healthcare experiences and related attitudes and practices, and what women see as the primary structural and social barriers to comprehensive care. Findings echo past literature about the inaccessibility of doctor's offices, including the lack of suitable exam tables. However, our findings also suggest that the lack of education and training among medical providers could be a key social barrier and determinant of whether individual women actually secure gynecological care.